Optimasi Suhu dan Waktu SSF untuk Produksi Bioetanol dari Sampah Daun Menggunakan Trichoderma Viride dan Zymomonas Mobilis - Wulan Fitriani Safari (Biotropic : The Journal of Tropical Biology, 2022)
Foliage from gardens or parks is biomass whose organic fraction can be decomposed. Foliage can be utilized by converting it into bioethanol. Various studies have shown that Trichoderma viride and Zymomonas mobilis play a role in the production of bioethanol from biomass, but until now there has been no report on the production of bioethanol from foliage using a mixture of  T. viride and Z. mobilis. The purpose of this study was to determine the optimal SSF temperature and time for bioethanol production from foliage using T. viride and Z. mobilis. The fermentation process used the Simultaneous Saccharification and Fermentation (SSF) method with a mixture of T. viride and Z. mobilis with a composition of 5% : 5% (w/v). SSF was carried out at several variations of time and temperature, 60 hours, 72 hours, 80 hours and 96 hours for times and temperatures used are 32oC, 35oC and 38oC. The fermented bioethanol was purified by distillation and finally, the ethanol content was tested with GC. Bioethanol was successfully produced from foliage using T. viride and Z. mobilis with the highest ethanol content obtained in SSF with a temperature of 35oC and a time of 72 hours, which is 0.2151%.